OsNLP3 and OsPHR2 orchestrate direct and mycorrhizal pathways for nitrate uptake by regulating NAR2.1–NRT2s complexes in rice - Shuangshuang Wang; Hanghang Ye; Congfan Yang; Yan Zhang; Jiawen Pu; Yuhan Ren; Kun Xie; Lingxiao Wang; Dechao Zeng; Haoqiang He; Haoyan Ji; Luis Rafael Herrera-Estrella; et al. (Proceedings of the National Academy of Sciences, 2025)
Nitrogen (N) is the most important essential nutrient required by plants. Most land plants have evolved two N uptake pathways, a direct root pathway and a symbiotic pathway, via association with arbuscular mycorrhizal (AM) fungi. However, the interaction between the two pathways is ambiguous. Here, we report that OsNAR2.1–OsNRT2s, the nitrate (NO 3 − ) transporter complexes with crucial roles in direct NO 3 − uptake, are also recruited for symbiotic NO 3 − uptake. OsNAR2.1 and OsNRT2.1/2.2 are coregulated by NIN-like protein 3 (OsNLP3), a key regulator in NO 3 − signaling, and OsPHR2, a major regulator of phosphate starvation responses. More importantly, AM symbiosis induces expression of OsNAR2.1 – OsNRT2s, OsNLP3, and OsSPX4 , encoding an intracellular Pi sensor, in arbuscular-containing cells, but weakens their expression in the epidermis. OsNAR2.1 and OsNLP3 can activate both mycorrhizal NO 3 − uptake and mycorrhization efficiency. Overall, we demonstrate that OsNLP3 and OsPHR2 orchestrate the direct and mycorrhizal NO 3 − uptake pathways by regulating the NAR2.1–NRT2s complexes in rice.